Synthesis of Ce/Gd@HA/PLGA Scaffolds Contributing to Bone Repair and MRI Enhancement - Song, Xianji; Liu, Xilin; Ma, Yihang; Zhu, Qingsan; Bi, Mingchao (Frontiers in Bioengineering and Biotechnology, 2022)
It is important for future clinical applications to design and synthesize multi-purpose scaffolding materials for bone tissue engineering with high osteogenic induction and MRI imaging capability. In the present work, we synthesized Ce/Gd@HA by co-doping Ce3+ and Gd3+ into HA (Hydroxyapatite) using a hydrothermal synthesis method. And then Ce/Gd@HA composites were synthesized by combining Ce/Gd@HA nanoparticles with Polylactic-Co-Glycolic Acid (PLGA) to investigate whether implanted Ce/Gd@HA/PLGA composites could promote osteoblast viability leading to tibia repair of the rats and enhance MRI. The measurement results contain X-ray diffraction (XRD), Fourier-transformed infrared (FT-IR) spectroscopy, and Environmental scanning electron microscopy (ESEM), showing that HA doped with Ce3+ and Gd3+ was still hexagonal crystal with high crystallinity. The synthesized Ce/Gd@HA/PLGA composites have structure and obvious magnetic resonance imaging capability. The in-vitro experimental results indicated that Ce/Gd@HA/PLGA composites significantly promoted the performances of MC3T3-E1 cells, containing proliferation, adhesion, and osteogenic differentiation capacities. These include the improvement of alkaline phosphatase activity, enhancement of mineral deposition, and upregulation of OCN and COL-1 gene expression. The in-vivo experimental results demonstrated that the Ce/Gd@HA/PLGA composites significantly improved the healing rate of rat bone defects. The MRI images indicated that the Ga-doped composites were observed in the MRI T1 sequence in rats. The above results suggested that Ce/Gd@HA/PLGA composites not only effectively promoted bone formation, but also enhanced MRI imaging capability. The composites synthesized in this work have great potential in bone regeneration in an extensive application of bone tissue engineering.